Analysis of Student Perception with Online Distance Learning during Covid-19 Pandemic - MUSTAFA, NUR NABILAH (Enhanced Knowledge in Sciences and Technology, 2022)
The majority of educational institutions have closed as a consequence of the COVID-19 pandemic, which has affected academic calendars. Educational institutions remained closed during the unlocking phases to protect the safety of students, educators, and their families. Online distance learning has been the preferred method of learning in Malaysia to continue academic activities during the pandemic. This study aims to ascertain Faculty of Applied Sciences and Technology (FAST) students’ perceptions of online distance learning by an online survey of 623 students. The analysis revealed that the most frequently utilized online platforms by lecturers and FAST students were Google Meet and Zoom for online interactive classes and WhatsApp for communication with students outside of class. According to students’ responses, online education can benefit students by allowing them to have leisure time (59.07%). The significant challenge for FAST students was related to their home learning environment, whereas their least significant challenge was sharing electronic gadgets with family members. Additionally, the findings indicated that the COVID-19 pandemic had the most detrimental effect on the students’ mental health. The survey discovered that students are having problems concentrating in class due to lack of sleep and are continually logging out of Google Meet due to a poor internet connection. The findings of the study will assist educational institutions, especially UTHM to take this online distance learning more successfully in the future and organize activities that can let students delight with this new normal.